Urinary and plasma oxytocin changes in response to MDMA or intranasal oxytocin administration. (December 2016) - Francis, Sunday M.; Kirkpatrick, Matthew G.; de Wit, Harriet; Jacob, Suma
Highlights: Urinary oxytocin levels increase after MDMA and intranasal oxytocin administration. In healthy adults urine and plasma oxytocin levels are correlated after taking MDMA. In ASD youths urine and plasma oxytocin levels are correlated after taking oxytocin. Abstract: Background: The neuropeptide oxytocin (OT) has received increased experimental attention for its putative role in both normal social functioning and several psychiatric disorders that are partially characterized by social dysfunction (e.g., autism spectrum disorders: ASD). Many human experimental studies measure circulating plasma levels of OT in order to examine the relationship between the hormone and behavior. Urinary OT (uOT) assays offer a simple, easy, and non-invasive method to measure peripheral hormone levels, but the correspondence between uOT and plasma OT (pOT) levels is unclear. Here, we conducted two within-subjects, double-blind studies exploring changes in uOT and pOT levels following administration of two drugs: MDMA, an oxytocin-releasing drug (Study 1), and intranasal oxytocin (INOT: Study 1 and 2). Methods: In Study 1, 14 adult participants (2 females) were each administered either oral 1.5 mg/kg MDMA or 40 IU INOT across two different study sessions. In Study 2, 10 male participants (adolescents and young adults) diagnosed with ASD received either 40 IU INOT or placebo across two different sessions. In both studies, blood and urine samples were collected before and after drug administration at each study session. For Study 1, 10 participants provided valid plasma and urine samples for the MDMA session, and 8 provided valid samples for the INOT session. For Study 2, all 10 participants provided valid samples for both INOT and placebo sessions. Pre- and post-administration levels of pOT and uOT were compared. Additionally, correlations between percent change from baseline uOT and pOT levels were examined. Results: Study 1: Plasma OT and uOT levels significantly increased after administration of MDMA and INOT. Furthermore, uOT levels were positively correlated with pOT levels following administration of MDMA (r = 0.57, p = 0.042) but not INOT (r = 0.51, p=0.097). Study 2: There was a significant increase in uOT levels after administration of INOT, but not after administration of placebo. Under both conditions, INOT and placebo, significant increases in pOT levels were not observed. Additionally, change from baseline uOT and pOT levels were positively correlated (r = 0.57, p=0.021). There was no significant correlation between uOT and pOT levels following placebo administration. Conclusion: Our results show a measurable and significant increase in pOT and uOT levels after the administration of MDMA (Study 1) and INOT (Study 1 and Study 2). Additionally, a positive correlation between uOT and pOT levels was observed in both samples (healthy adults and ASD patients) in at least one condition. However, uOT and pOT levels were not correlated under all conditions, suggesting that uOT levels do not fully correspond to pOT levels in the time windows we measured. Future studies should further examine the relationship between levels of pOT and uOT in healthy and clinical populations on measures of social behavior because uOT may serve as an additional non-invasive method to measure peripheral OT changes.